The implication of pro-inflammatory cytokines in the impaired production of gonadal androgens by patients with pulmonary tuberculosis - Bini, Estela Isabel (2015)
Background: The chronic nature of tuberculosis and the protracted immuno-inflammatory reactions are implied in a series of metabolic and immune-endocrine changes accompanying the disease. We explored components from the hypothalamous-pituitary-gonadal axis and their relationship with cytokines involved in disease immunopathology, in male TB patients. Methods Plasma samples from 36 active untreated pulmonary TB male patients were used to determine TNF-α, IFN-γ, TGF-β, IL-6, cortisol, dehydroepiandrosterone, testosterone, progesterone, estradiol, luteinizing hormone (LH) and follicle-stimulating hormone (FSH) by ELISA. Healthy controls corresponded to 21 volunteers without contact with TB patients and similar age (40 ± 16,8 years). Testicular histological samples from necropsies of patients dying from TB were immune-stained for IL-1β, TNF-α, IL-6 and IFN-γ. The TM3 mouse Leydig cell line was incubated with recombinants TNF-α, IFN-γ and TGF-β, supernatants were collected and used to measure testosterone by ELISA. Results Patients showed decreased levels of testosterone in presence of high amounts of LH, together with augmented IFN-γ, IL-6 and TGF-β levels. Testicular histological sections showed abundant presence of IL-1β, TNF-α, IL-6 and IFN-γ in interstitial macrophages, Sertoli cells and some spermatogonia. In vitro treatment of Leydig cells with these cytokines led to a remarkable reduction of testosterone production.